TYPES AND EFFECTIVENESS OF ADAPTATION STRATEGIES ON CLIMATE CHANGE: LESSON LEARNED FROM DAERAH ISTIMEWA JOGYAKARTA - Sri Wahyuni; Saptana Saptana (UPT Penerbitan Universitas Jember, 2012)
This paper consist of types of adaptation strategies and its effectiveness of the various adaptation strategies carried out by farmers in Daerah Istimewa Yogyakarta. Theresearch done during 2011 fiscal year, data collected from 10 groups of farmersexperienced with floods and 10 groups with drought impact of climate change and theinformation presented descriptively. The effectiveness of adaptation strategies evaluatedthrough the ratio of income to cost of rice production (R/C), both for adaptation conditions(R/Ca) and normal conditions (R/Cn). For flood, types of anticipative adaptation were changing commodities, changing planting system and making drainage channels andmaintaining/deepening of drainage channels. The responsive adaptation were croppingpattern adaptation, changing commodities, planting submerged of resistant seed of rice andimplementing appropriate dose of fertilizer. For drought, anticipative adaptation weremaking a dam, creating joined or share wells and provides drilled/pump wells. Theresponsive adaptation were changing Varieties and commodities. The effectivenessstrategy adaptation on flood were effective, with value of R/Ca ratio 1:09 while R/Cn 1:56. In drought adaptation almost effective since the value of R/Ca 0.93 and R/Cn 1:48.